Sulfonamide Inhibitors of β‐Catenin Signaling as Anticancer Agents with Different Output on c‐MYC. (14th October 2020) - Di Magno, Laura; Di Pastena, Fiorella; Puxeddu, Michela; La Regina, Giuseppe; Coluccia, Antonio; Ciogli, Alessia; Manetto, Simone; Maroder, Marella; Canettieri, Gianluca; Silvestri, Romano; Nalli, Marianna
Abstract: The Wnt/β‐catenin pathway is often found deregulated in cancer. The aberrant accumulation of β‐catenin in the cell nucleus results in the development of various malignancies. Specific drugs against this signaling pathway for clinical treatments have not been approved yet. Herein we report inhibitors of β‐catenin signaling of potential therapeutic value as anticancer agents. Ethyl 4‐((4‐(trifluoromethyl)phenyl)sulfonamido)benzoate (compound 14 ) inhibits the effect on Wnt reporter with an IC50 value of 7.0 μM, significantly reduces c‐MYC levels, inhibits HCT116 colon cancer cell growth (IC50 20.2 μM), does not violate Lipinski and Veber rules, and shows predicted Caco‐2 and MDCK cell permeability P app >500 nm s −1 . Compound 14 seems to have potential for the development of new anticancer therapies. Abstract : A small test set of sulfonamides was synthesized to further explore this class of Wnt/β‐catenin inhibitors. Compound 14 inhibits HCT116 colon cancer cell growth with an IC50 value of 20.2 μM. It has an effect on the Wnt reporter with an IC50 value of 7.0 μM in HEK293T cells, and significantly reduces c‐MYC levels. Compound 14 shows potential for the development of new anticancer agents.